The “New Face" of Capitalism as a Basis for the Historical-sociological Analysis of the Evolution of Inequality. Book Review: Haskel J., Westlake S. (2024). Capitalism without Capital: The Rise of the Intangible Economy. Moscow: Publishing House of the Higher School of Economics. - I. V. Trotsuk (Социология власти)
.